Waste Not, Plant, Rot: A wastewater treatment centre that produces sustainable resources in Norwood, Johannesburg - Glanville, Robyn Alice (University of the Witwatersrand, Johannesburg, 2024)
This research investigates the delivery of essential resources - water, energy, and food around Orange Grove and Norwood, Johannesburg, where all three aspects are threatened by pollution and inaccessibility. Drawing upon permaculture and biomimicry principles, the study explores localized resource management in neighbourhood nodes to address the pressing issue of sustained inequality in South Africa. Focusing on a wastewater treatment plant and an aquaponic farm in Orange Grove, Johannesburg, the project aims to generate sustainable materials, produce, clean water, and energy while fostering spatial and social justice opportunities through community engagement and learning.
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Architecture (Professional) in 2024.
Keywords: Norwood; Orange Grove; Johannesburg; Water treatment; Aquaponics; Parks; Local labour; Phytoremediation; Bamboo; 3D printed; Urban design; 15 minute City; Decentralised resources; Resource generation; Biogas; UCTD; SDG-11: Sustainable cities and communities